Multiple utility concepts – individual choice as an outcome of a game - Musialik, Grażyna; Musialik, Rafał (Koncepcje użyteczności wielokrotnej – wybór podmiotu jako wynik gry, 2019)
The paper aims to analyse individual choices within the framework of multiple utility concepts. These concepts are based on the assumption that people, while making their choices, strive for more than one value, and respectively make more than one ordering of bundles of goods or states of affairs. The paper presents, first of all, the relations between the notion of utility and the notion of the ordering of bundles of goods (states of affairs). Secondly, it discusses the mechanisms governing the individual choices suggested on the grounds of the multiple utility theory. In particular, an important issue of these theories is identified, namely, the matter of choice when one faces incommensurable values. Thirdly, G. Kavka’s idea is taken into consideration, enabling its solution. Its crucial features are described, enabling, as it seems, to build a formal model of individual choice in the case of incommensurable values. The paper is based on the analysis of the subject-related literature and its content is of a theoretical nature only
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 108-117
Keywords: multiple untility; consumer theory; rational choice; teoria konsumenta; użyteczność wielokrotna; racjonalny wybór